Gel‐casting of MgAl2O4 transparent ceramics using a common dispersant. Issue 6 (25th January 2019) - Liu, Mengwei; Shimai, Shunzo; Zhao, Jin; Zhang, Jian; Han, Dan; Li, Yi; Liu, Juan; Wang, Shiwei
Abstract: The ethanolaminic salt of citric acid (commercial name Dolapix CE 64) has commonly been used as a dispersant for colloidal based ceramic forming process. In this paper, a surprise was presented that MgAl2 O4 spinel slurries consisting of MgAl2 O4 spinel nanoparticles and Dolapix CE 64 gelled in air at room temperature spontaneously. The MgAl2 O4 spinel slurries with high solid loading (54 vol%) were prepared with Dolapix CE 64 and the green body with up to 57% relative density was obtained. MgAl2 O4 transparent ceramics with small grain size (0.92 μm) and high transmittance (81.7% at 600 nm) were fabricated after pre‐sintering at 1500°C and hot‐isostatic sintering at 1550°C.